The role of perceptual salience in the L2 acquisition sequence of the Arabic construct state. (20th February 2017) - Azaz, Mahmoud; Frank, Joshua
Abstract : Perceptual salience has been proposed as an essential factor in the order in which various linguistic phenomena are acquired. This study examines its influence on the acquisition sequence of a single construction, which is the Arabic construct state. Mapping certain English constructions to the definite Arabic construct state entails restructuring head direction (a feature of high salience) and the position of the definite marker (a feature of low salience). Results from a prompted sentence completion task suggested that early English‐speaking learners of Arabic were sensitive to head direction but not definiteness. Analysis of intermediate and advanced groups captured the acquisition sequence of the Arabic construct state, proceeding in two gradual phases. During the first phase, English‐speaking learners restructure head direction. Only later do they adjust definiteness.